Experimental Results on Bistatic Radar Based on 5G OFDM Synchronization Signal - Van Tuan Nguyen (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Orthogonal frequency division multiplexing (OFDM) has become a popular wideband digital communication scheme. Research studies into the use of new telecommunication signals, including those synthesized based on the 5G standard, in bistatic radar indicate the possibility of providing high resolution in terms of range and speed. In comparison with, e.g., a digital video broadcasting signal on the ground (DVB-T), 5G transmission depends on the user demand. In the absence of active users, the 5G downlink signal includes only the synchronization signal block (SSB), which is constantly present. Research into the possibility of using the 5G synchronization block in bistatic radar represents a relevant task, enabling radar monitoring in areas where the use of 5G has not yet been sufficiently developed among the population.Aim. Analysis of 5G synchronization signal, simulation of signal processing in bistatic radar, and conducting analysis of experimental results.Materials and methods. The research was conducted using the theory of signal processing in bistatic radar, the standard and structure of the 5G synchronization block signal, and comparative analysis. The cross-ambiguity function of bistatic radar was calculated by computer simulation in MATLAB and by experimental studies. A passenger car (Hyundai ix35) was used as the object of observation. Signals were received and recorded using the Ettus USRP B210 SDR platform.Results. Simulation and experimental studies were conducted in the 5G signal coverage area. The results obtained show that a bistatic radar system based on the 5G synchronization signal block is capable of detecting moving targets.Conclusion. The 5G synchronization signal block produces satisfactory results when determining the range. At the same time, the speed cannot be measured precisely. In order to eliminate the ambiguity when measuring the speed, we propose to use a two-stage signal synthesized based on OFDM, with different repetition periods of synchronization signals and subsequent multiplicative processing. A bistatic radar system based on SSB 5G can become one of the subsystems for monitoring vehicles.